Data structures using C - Thareja, Reema (Oxford higher education, 2018)
The second edition of Data Structures Using C is designed to serve as a textbook for undergraduate engineering students of computer science as well as postgraduate students of computer applications. It provides a comprehensive coverage of the concepts of data structures and their implementation using C language.